Teacher Identified Professional Learning Needs to Effectively Include a Child With Down Syndrome in Primary Mathematics. Issue 2 (June 2016) - Faragher, Rhonda; Clarke, Barbara
Abstract: The practices of effective primary school teachers including students with Down syndrome in their mathematics classes are largely unexplored and many teachers feel unprepared to teach students with an intellectual disability. The authors sought to find out what these specific professional learning (PL) needs were and if they changed over time. A mixed methods study was undertaken to investigate the practices of primary mathematics teachers including students with Down syndrome in regular class lessons in two Australia educational jurisdictions. A variety of approaches was used to gain an understanding of their practices. Findings are based on responses to a questionnaire administered to teaching teams at the beginning and end of the school year. There was a strong endorsement of inclusion as an appropriate practice in primary mathematics. The PL needs of teaching teams changed across the teaching year. Early requirements concerned understanding Down syndrome and its impact on learning and behavior. As the school year progressed, PL needs changed toward a greater focus on the need for specific resources and strategies for teaching mathematics. The PL requirements of teachers included the need for "in‐time" support. The authors conclude that even if it may be infrequent when a teacher has a student with Down syndrome in a mathematics class, teachers still need access to PL that evolves across the school year, from less focus on syndrome‐specific information to greater emphasis on teaching mathematics through adjusting learning outcomes and teaching approaches.